THE TECHNOLOGY CASE OF SHRIMP TRAWL IN RAJA BEJAMU VILLAGE, SINABOI DISTRICT, ROKAN HILIR, RIAU PROVINCE. - Alan Budiardi; Pareng Rengi; Arthur Brown (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted on August 2014, in Raja Bejamu Village, Sinaboi District, Rokan Hilir, Riau Province. The purpose of this study was to determine the friendly environmental level and the feasibility of shrimp trawl fishing gear.This research used a survey method, which is do a directly observation of shrimp trawl fishing gear by measuring the dimensions and the amount of catches.The catches of shrimp trawl consists of red shrimp species 35 Kg, Swallow shrimp 29 Kg and by catches are namely flounder 13 Kg, ikan gulamah 18 Kg , shrimp centipede size A 1 and crab 2 crabs.From the results of the feasibility calculations showed that the shrimp trawl gear is profitable and feasible to be continued and from the calculation of friendly environmental showed that shrimp trawl gear isn’t a friendly environmental gear.Keyword: Shrimp trawl, catches, feasibility, friendly environmental.